Determinan Pencegahan Kecurangan dalam Pengelolaan Dana LPD - Putu Satcitananda Dewi; Made Arie Wahyuni (Universitas Pendidikan Ganesha, 2020)
This study aimed to obtain evidence of the effect of organizational culture, histleblowing, internal control systems, and individual morality on fraud prevention in the management of LPD funds. This study used numerical analysis of these variables, therefore esearchers use a quantitative approach. The population in this study were all employees working in LPDs in Karangasem sub-district, as many as 57 employees. The sample in this study as determined by saturation sampling (census) which means that the entire population was made a research sample. Data were collected using a questionnaire with Likert scale. Then the data were analyzed using regression analysis tests with the help of SPSS version 18. The results showed that organizational culture, whistleblowing, internal control systems and Individual morality has a positive effect on fraud prevention.